Methodologies for project sustainability - Motta – Sanjuan, Yesenia (Universidad Francisco de Paula Santander, 2018)
When talking about projects today, a relevant component for their management also appears, such as sustainability. Theme that groups various aspects among which are the methodologies, measurements and models, which give way to evaluate the sustainable processes developed by every project leader, so they are usually complementary techniques and tools that measure the impact of the processes within the social, economic and environmental dimensions. Under this approach, this review article is presented, which seeks to study and analyze the world of projects in response to their development within the framework of value generation within a globalized and dynamic environment. Specifically, the management of projects is specified according to compliance with sustainability standards based on principles of social responsibility that reflect their contribution within the exercise of cooperativity and general development of the system. The idea then is to address sustainability from the planning, direction and control of projects, where it is constituted as a key element for management supported by methods.